Smještaj gradskog plemstva u dalmatinskim gradovima srednjeg vijeka - Benyovsky, Irena (Acta Histriae, 2008)
During the Middle Ages the distribution of urban plots and erection of buildings depended on the societal structures that participated in the construction of the town and on general processes characterizing this period. The right to own property and the size of the property were among the most important status symbols of the urban nobility, and thus patrimony and nobility were closely interrelated. Noble families strived for close relations among family members, which is why new houses of members of the same family would be built in close proximity to the first house. The accumulation of real estate in the town (i.e., several plots of land with buildings or without them) enabled subsequent functional or architectural changes to defined zones within the town. Therefore, numerous property-legal relations in this framework can be found in medieval Dalmatian towns, as is revealed by the case of Trogir and preliminary research findings in Dubrovnik and Zadar.
Keywords: Dalmacija; Dalmatia; mesta; mestno plemstvo; Middle Ages; plemstvo; socialna topografija; srednji vek